Image Compression Using Vector Quantization and Genetic Algorithms - Awad Salman, Salah (Anbar Journal of Engineering Sciences, 2008)
Image compression involves reducing the size of image data file, while retaining necessary information.This paper uses the facilities of the Genetic Algorithm for the enhancement of the performance of one of the popular compression method, Vector Quantization method is selected in this work. After studying this method, new proposed algorithm for mixing the Genetic Algorithm with this method was constructed and then the required programs for testing this algorithm was written. The proposed algorithm was tested by applying it on some image data files. Some fidelity measures are calculated to evaluate the performance of the new proposed algorithm. A good enhancement was recorded for the performance of the Vector Quantization method when mixed with the Genetic Algorithm. All programs were written by using Matlab (version 7.0) and these programs were executed on the Pentium III (866 MHz) personal computer.